Improving mathematical communication and critical thinking in middle school students: Study of anchored instruction learning assisted by edpuzzle - Vidyastuti, Annisa Nurina; Baiduri, Baiduri; Inganah, Siti; Hagenimana, Emmanuel (Universitas Islam Raden Intan Lampung, INDONESIA, 2023)
Background: Mathematics learning often appears unattractive to students due to its monotonous, intimidating, and boring nature. Active engagement in learning mathematics requires students to effectively utilize their communication and critical thinking skills.Aim: This study aims to 1) analyze the critical thinking abilities of students in a learning context, 2) assess their written and oral mathematical communication abilities, 3) evaluate their critical thinking skills in problem-solving, and 4) explore the impact of the Anchored Instruction learning setting assisted by Edpuzzle on these competencies.Method: Employing a descriptive qualitative research design, this study involved 24 VII-H grade students from SMPN 8 Malang. Data were collected using observation sheets, worksheets, and test questions.Results: The study indicates significant improvements in students’ critical thinking and mathematical communication skills. Critical thinking, observed through increased and more sophisticated student participation, was categorized as high in 5 students, medium in 16, and low in 3. Similarly, in mathematical communication, 5 students excelled, 13 were above average, and 6 were below average. This progression exhibited the effectiveness of the Anchored Instruction learning setting assisted by Edpuzzle in enhancing these skills.Conclusion: The study concludes that the Anchored Instruction learning setting, supported by Edpuzzle, significantly enhances students' critical thinking and mathematical communication abilities. This approach has proven effective in engaging students more actively in the learning process and improving their problem-solving skills.